Analisa Pengaruh Kerapatan Udara dan Tegangan Kritis Kawat Penghantar Terhadap Rugi Rugi Daya Corona Sutet 275 kV - Alfajri, Dio (Journal on Pustaka Cendekia Informatika, 2023)
This research aims to calculate the effect of the condition of the conducting wire on the 275 kV corona power losses in the Kiliran Jao - Payakumbuh area. This calculation aims to obtain the value of the power losses caused by air density and critical voltage. It can be explained that the value of power losses that occur during one year from August 2022 to July 2023 where the value of power losses varies from 4.94 KW/km to 4.23 KW/km. Where in August 2022 the power loss value is 4.49 KW/km, in September 2022 the power loss value is 4.36 KW/km, in October 2022 the power loss value is 4.23 KW/km, in in November 2022, the power loss value is 4.36 KW/km, in December 2022, the power loss value is 4.49 KW/km, in January 2023, the power loss value is 4.57 KW/km, in February In 2023, the value of power loss was 4.57 KW/km, in March 2023, the value of power loss was 4.81 KW/km, in April 2023, the value of power loss was 4.94 KW/km, in May 2023, the value of power loss loss is 4.81 KW/km, in June 2023 the value of power loss loss is .57 KW/km, in July 2023 the value of power loss loss is 4.57 KW/km. Based on the calculation above, it can be concluded that if If the critical voltage value increases, the power loss value will decrease and if the critical voltage value increases, the power loss value will decrease.